Transnasal Esophagoscopy Procedure in Outpatient Clinic at Dr. Soetomo General Academic Hospital - Muhammad Qodri Anantomo; Rizka Fathoni Perdana (Indian Journal of Forensic Medicine & Toxicology, 2022)
Background: Transnasal esophagoscopy is a small caliber flexible esophagoscopy technique that has the same as diagnostic accuracy as conventional esophagoscopy. In addition, this technique is safer than any other techniques and has patient tolerance. Aims: This study aims to analyze and evaluate the transnasal esophagoscopy (TNE) procedure in patients. Method: retrospectively approach was used in this study by taking data from the activity register of the broncho-esophagology division of outpatient unit of ORL-HNS Dr. Soetomo General Academic Hospital. TNE report book and patient medical records were collected to have the data. The observation period was 2013 to 2017. Result: patients who met the inclusion and exclusion criteria was 99 patients, with a male to female ratio of 2.3: 1. Most endoscopic findings were normal esophagus (56.57%). Existing abnormal findings included esophageal stenosis (18.18%), esophageal mucosal lesions (14.14%), and esophageal tumors (11.11%). TNE examination complications were found to be 1%. Conclusion: Transnasal esophagoscopy is widely used in patients aged 51-60 years with dysphagia, reflux or globus as the most common indications. TNE is quite safe to do in an outpatient hospital setting.